Effects of script-based role play in cardiopulmonary resuscitation team training. Issue 8 (1st September 2010) - Chung, Sung Phil; Cho, Junho; Park, Yoo Seok; Kang, Hyung Goo; Kim, Chan Woong; Song, Keun Jeong; Lim, Hoon; Cho, Gyu Chong
Abstract : Background: The purpose of this study is to compare the cardiopulmonary resuscitation (CPR) team dynamics and performance between a conventional simulation training group and a script-based training group. Methods: This was a prospective randomised controlled trial of educational intervention for CPR team training. Fourteen teams, each consisting of five members, were recruited. The conventional group (C) received training using a didactic lecture and simulation with debriefing, while the script group (S) received training using a resuscitation script. The team activity was evaluated with checklists both before and after 1 week of training. The videotaped simulated resuscitation events were compared in terms of team dynamics and performance aspects. Results: Both groups showed significantly higher leadership scores after training (C: 58.2±9.2 vs 67.2±9.5, p=0.007; S: 57.9±8.1 vs 65.4±12.1, p=0.034). However, there were no significant improvements in performance scores in either group after training. There were no differences in the score improvement after training between the two groups in dynamics (C: 9.1±12.6 vs S: 7.4±13.7, p=0.715), performance (C: 5.5±11.4 vs S: 4.7±9.6, p=0.838) and total scores (C: 14.6±20.1 vs S: 12.2±19.5, p=0.726). Conclusion: Script-based CPR team training resulted in comparable improvements in team dynamics scores compared with conventional simulation training. Resuscitation scripts may be used as an adjunct for CPR team training.